2001
DOI: 10.1002/ajmg.10166
|View full text |Cite
|
Sign up to set email alerts
|

Association of tetralogy of Fallot with a distinct region of del22q11.2

Abstract: Congenital heart defects (CHDs) appear in greater frequency among relatives of patients and in individuals with DiGeorge syndrome (DGS) or velo-cardio-facial syndrome (VCFS). A majority of these patients and part of the apparently nonsyndromic CHD patients with conotruncal defects manifest hemizygous deletions within chromosome 22q11.2 (del22q11). We tested myocardial tissues of 31 CHD patients, 21 with tetralogy of Fallot (TOF) and 10 with a double-chamber right ventricle (DCRV). DNA isolated from tissues rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…There was no microsatellite marker loci deletion in the 22a11.2 region of five ASD patients. In 2002, Kessler-Icekson et al reported that 48% of TOF patients had homozygosity for three or more consecutive marks, indicating deletions of various sizes [15]. Our incidence of 22q11.2 deletion with TOF was 50%, which is similar to Kessler-Icekson et al's report.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was no microsatellite marker loci deletion in the 22a11.2 region of five ASD patients. In 2002, Kessler-Icekson et al reported that 48% of TOF patients had homozygosity for three or more consecutive marks, indicating deletions of various sizes [15]. Our incidence of 22q11.2 deletion with TOF was 50%, which is similar to Kessler-Icekson et al's report.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on isolated TOF/PDA indicated the existence of gene haploid loss in the 22q11.2 region [15]. Although most authors did not think there was a relationship between isolated CHD and 22q11.2 deletion [4][5][6][7], our result here is not only consistent with Wilson et al's report that chromosome 22 deletions were detected in isolated familiar CHD [8,9], but also consistent with McElhinney et al's finding that chromosome 22q11 deletion was associated with isolated anomalies of laterality or branching of the aortic arch [10].…”
Section: Discussionmentioning
confidence: 99%
“…In general, CTDs are the disorders most commonly associated with the 22q11.2 deletion syndrome [22,23]. Of the study subjects, 20% (7/35) of those with PA/VSD, 5.4% (4/74) with TOF, 33% (1/3) with PTA and 2% (1/51) with DORV were detected to have the 22q11.2 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate critical genes for major features of DGS are thought to include HIRA , TBX1 and COMT [McDonaldMcGinn et al, 1999;Lindsay et al, 2001;Kessler-Icekson et al, 2002;Bearden et al, 2004;Prasad et al, 2008;Chen et al, 2014;Ogata et al, 2014]. CRKL is considered a candidate critical gene for the central deletions [Racedo et al, 2015], and MAPK1/ERK2 for the distal type I deletions [Saba-El-Leil et al, 2003;Binétruy et al, 2007;Newbern et al, 2008;Samuels et al, 2008].…”
Section: Variability Of Phenotypementioning
confidence: 99%